Impacts of climate policies on industrial competitiveness in Korea - Hyunseok Kim (Korea Development Institute (KDI), 2022)
As carbon reduction targets are being strengthened globally, it is increasingly important in Korea to comprehend the impact of two major greenhouse gas (GHG) reduction policies, Target Management System (TMS) and Emissions Trading System (ETS), on industrial competitiveness. ETS relies more on individual firms' economic incentives compared to TMS, which is a command-andcontrol regulation. While the transition from TMS to ETS in 2015 is found to have partially alleviated the burden for manufacturing firms, there is a need to enhance policy effectiveness by acknowledging their limited performance in reducing carbon emissions thus far. While TMS was introduced in 2011 with the aim of enforcing emissions reduction and enhancing energy efficiency across different sectors, heavy emitters have been managed separately through ETS since 2015. Knowing the low abatement performance in the manufacturing industry after mid-2010, the reduced burden can be attributed to two factors: i) improvement in efficiency resulting from the transition, and ii) alleviation of the burden through the provision of free allocations. The policy efforts should aim for a greater reduction by strengthening the targets for the regulated firms, which is in line with the reinforced policy goals announced in October 2021. Stricter goals are inevitable in the future, and therefore, policymakers must endeavor to bolster the sustainability of the manufacturing sectors by developing a detailed roadmap based on multiple indicators. Taking into account the varying impacts of GHG reduction policies on the competitiveness based on the energy intensity and emission intensity of each sector, the roadmap needs to be carefully crafted in order to impose a feasible burden on the regulated firms.
Keywords: 330